Effect of Bi2O3 on the properties of linier low density polyethylene (LLDPE)/natural rubber compound (NRC) composites - Dwi Wahini Nurhajati; Umi Reza Lestari; Ike Setyorini (Majalah Kulit, Karet, dan Plastik, 2020)
The use of thermoplastic natural rubber (TPNR) has spread for many applications such as in footwear, hoses, seals, and automobiles. This increase is in line with the environmental awareness to produce materials that can be recycled. In this paper, the making of TPNR for car floor mat was studied. Bi2O3 filler was added to modify the performance of TPNR for car floor mat. In this study, the effects of Bi2O3 filler on the properties of linear low-density polyethylene (LLDPE)/natural rubber (NR) composites had been investigated. The weight ratio of LLDPE/NR was varied at 90/10; 80/20; 75/25; and 70/30. Bi2O3 filler loading was varied at 0; 20; 40; and 50 phr. The increase in NR and Bi2O3 filler reduced the tensile strength, elongation at break, and tear resistance, but increased the hardness and density of the composites. Compared to similar imported products, the samples prepared in this study showed higher values for all mechanical properties (tensile strength, elongation at break, tear resistance) but lower values in density. Scanning electron microscopy (SEM) micrograph of LLDPE/NR 75/25 composites either with or without the addition of 20 phr Bi2O3 filler displayed homogeneity of the mixture.